Safety of nimotuzumab following clinical trials in head and neck epithelial tumors - Oneyda Clapé-Laffita; María V. Perrand-Roberts; Milagros Domecq-Salmon; Maryenis Rodríguez-Alfaro; Maritza Cebreco-Sardina (GarVal Editorial Ltda., 2021)
Context: Immunotherapy, by directing the immune response against tumor cells, complements the oncological therapy along with conventional treatments. Thus, the monoclonal antibody nimotuzumab blocks the binding of epidermal growth factor to its receptor, interfering with cell proliferation in epithelial tumors, such as those of the head and neck. Aims: To evaluate the safety of nimotuzumab after concluded the clinical trials in epithelial tumors of the head and neck, analyzing the relation with the therapeutic compliance for the patients. Methods: A retrospective descriptive study was carried out, characterizing nine patients with epithelial tumors of the head and neck, who continued to use nimotuzumab after concluding clinical trials; and evaluating adverse effects according to severity, intensity, causality, and frequency, thus establishing the safety of this medicine. The compliance of nimotuzumab therapy was analyzed, by reviewing the administration intervals to the received doses. A descriptive statistical analysis was performed. Results: In the studied sample men predominated (eight patients: 88.89%), without significance differences in age and race. All were diagnostic with epidermal carcinomas, predominated the good differentiated (six patients: 66.67%). Five adverse effects were detected in two old patients (all not serious, light or moderate, and possible or probable, occasional or frequent), evaluating to nimotuzumab as safe medication. There was inadequate therapeutic compliance to treatment, not relation with the presented adverse effects. Conclusions: Nimotuzumab represented a safe drug after concluded the clinical trials in patients with epithelial tumors of the head and neck, without relation with the existed inadequate therapeutic compliance.